Superstructure of a Substituted Zeolitic Imidazolate Metal–Organic Framework Determined by Combining Proton Solid‐State NMR Spectroscopy and DFT Calculations1. (25th March 2015) - Baias, Maria; Lesage, Anne; Aguado, Sonia; Canivet, Jerome; Moizan‐Basle, Virginie; Audebrand, Nathalie; Farrusseng, David; Emsley, Lyndon
Abstract We report the supercell crystal structure of a ZIF‐8 analog substituted imidazolate metal–organic framework (SIM‐1) obtained by combining solid‐state nuclear magnetic resonance and powder X‐ray diffraction experiments with density functional theory calculations.